Understanding Consumer Motivations Behind Choosing Vegan Food Products - Bedi, Kanika (Digital Repository of Theses, 2025)
The increasing global adoption of veganism is driven by ethical, environmental, health, and social factors. This study explores consumer motivations behind choosing vegan food products, aiming to understand key drivers such as health consciousness, ethical considerations, environmental concerns, and social influences. The research also examines demographic variations, barriers to vegan consumption, and the broader implications for businesses and policymakers. A mixed-methods approach was employed, combining quantitative surveys with qualitative interviews to gain a comprehensive understanding of consumer behavior. The survey targeted a diverse sample of consumers, assessing their motivations, awareness, and purchasing behaviors. In-depth interviews provided richer insights into individual decision-making processes, challenges, and personal experiences with veganism. The collected data were analyzed using statistical and thematic analysis to identify key patterns and trends. Findings reveal that health-related concerns, particularly the perceived benefits of plant-based diets in reducing risks of chronic diseases such as heart disease, obesity, and diabetes, are a major driver of vegan food choices. Ethical considerations, including animal welfare and cruelty-free consumption, also play a critical role in shaping consumer preferences. Additionally, environmental awareness, particularly concerns about climate change, deforestation, and resource depletion, significantly influences individuals’ decisions to choose vegan food products. Despite the rising popularity of veganism, barriers to adoption persist. Higher costs, limited accessibility, taste preferences, and a lack of education about plant-based nutrition remain significant challenges. Demographic differences were evident, with younger consumers more inclined toward environmental and ethical concerns, while older consumers prioritized health benefits. Social influences, including peer networks, media advocacy, and cultural factors, further shape consumer attitudes and behaviors. The study concludes that addressing these motivations and barriers is essential for businesses, policymakers, and marketers seeking to expand the vegan food market. Improving affordability, increasing product availability, and enhancing education on plantbased nutrition can help drive greater consumer adoption. This research contributes to the growing literature on consumer behavior and ethical consumption, providing actionable insights to support the continued growth of the vegan food industry and promote sustainable, health-conscious dietary choices.